The impact of environmental disclosure and the quality of financial disclosure and IT adoption on firm performance: Does corporate governance ensure sustainability? - Lin, Jing; Qamruzzaman, Md (Frontiers in Environmental Science, 2023)
Introduction: The study’s motivation is to investigate the role of environmental and financial disclosure, IT adoption, and good governance on firms’ sustainability from 1990–2019. A sample of 75 financial institutions enlisted in Bangladesh’s capital market was considered for relevant data collection. Methodology: Secondary data sources were used for data accumulation, including annual reports of target FIs, economic review reports, and central banks publication. Several econometrical techniques have been implemented to document the empirical nexus and the elasticities of explained variables on firm performance. Findings: In terms of baseline assessment, the study revealed a positive and statistically significant association between a firm’s sustainability and target explanatory variables. Furthermore, the study extended the empirical valuation by implementing a system-GMM and documented a positive linkage between financial and environmental disclosure, IT adaptation, good governance, and the firm’s performance sustainability. Discussion: These study findings suggest that information symmetry, investor protection, and access to financial services foster and stabilize the firms’ performance. Concerning corporate governance’s mediating effect, the study established a mediating role with positive influences on financial performance augmentation. On the policy ground, the study postulated that financial policymakers should address fairness and integrity in disclosing information to the public. Enforcement has to be initiated to ensure good governance.